2015
DOI: 10.1002/pbc.25773
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Late Effects in Pediatric Cancer Survivors: A Report From the Children's Oncology Group

Abstract: Background This review was conducted to update the Children’s Oncology Group (COG) Long-Term Follow-Up Guidelines (COG-LTFU Guidelines; version 4.0) regarding screening for psychosocial late effects of pediatric cancer. Procedure Articles published between August 2009 and January 2011 that addressed psychosocial late effects of long-term survivors of pediatric cancer (n = 35) were reviewed by a multidisciplinary team of COG late effect experts. Results The majority of studies in this time period indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 55 publications
9
97
2
5
Order By: Relevance
“…Patients and parents emphasized many positives, including having extremely supportive friends and a global sense of having good peer relationships. These findings are consistent with broader literature on pediatric cancer survivors demonstrating positive psychosocial adjustment, resilience, benefit‐finding, and posttraumatic growth …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients and parents emphasized many positives, including having extremely supportive friends and a global sense of having good peer relationships. These findings are consistent with broader literature on pediatric cancer survivors demonstrating positive psychosocial adjustment, resilience, benefit‐finding, and posttraumatic growth …”
Section: Discussionsupporting
confidence: 89%
“…As survival rates for pediatric cancer have improved, increasing attention has shifted to survivors’ psychosocial well‐being. Although many survivors are well adjusted, psychosocial late effects have also been identified . Pediatric cancer survivors may experience social difficulties including social competence deficits, impaired peer relationships, fewer best friends, and more peer conflict and social withdrawal, compared with controls or sibling controls .…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver report before and after therapy completion suggested that obtaining information related to late effects of pediatric cancer treatment is a priority. As potential late effects range from physiological to cognitive to psychosocial, education should be tailored to individuals based on their disease and treatment. Additional information desired by parents during the transition period included information related to emotional and physical health and well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…13 Survivors of childhood cancer also have increased rates of suicidal ideation, anxiety, and global distress. 14 …”
Section: Introductionmentioning
confidence: 99%